Produksi IAA oleh Rhizobium sp. dalam medium sintetik dan serum lateks dengan suplementasi triptofan Indole acetic acid production by Rhizobium sp. on synthetic and latex serum media with tryptophan supplementation - . SUHARYANTO; . TRI-PANJI; . GUSNANIAR (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2009)
AbstractThe utilization of latex effluent to producebioproduct like indole acetic acid (IAA) willreduce amount of effluent, as well as effluentprocessing cost and produce an economicallyprofitable product. IAA could be produced bysome rhizosphere microbes that could grow onlatex effluent using L-tryptophan (Trp) as itsprecursor. The aim of this research is todetermine potential growth and capability of IAAproduction by Rhizobium spp. R6 and KT onsynthetic and latex serum media supplementedwith pure Trp and with litter poultry manure as acheap source of Trp. The research coveredexamination of IAA producing Rhizobia usingliquid synthetic media supplemented with 0.07g/L and 0.14 g/L Trp. The potential Rhizobiumsp. in producing IAA was then inoculated intolatex serum media supplemented with pure Trpand Trp from litter poultry manure. Result of theresearch showed that the highest IAA productionwas reached as much as 51.08 µg/mL in syntheticmedia supplemented with 0.14 g/L Trp inoculatedwith Rhizobium sp. R6. IAA could be producedas much as 6.63 µg/mL in pasteurizedundiluted latex serum media supplemented with0.14 g/L Trp. Using latex serum mediasupplemented with Trp from litter poultry manureshowed that Rhizobium sp. R6 could produce11.91 µg/mL. Supplementation of pure syntheticTrp in IAA production could be replaced withlitter poultry manure as a cheap source of Trp.AbstrakPemanfaatan limbah lateks menjadi produkbio seperti asam indol asetat (IAA), dapatmengurangi volume limbah, menekan biayapengolahan limbah, serta menghasilkan produkyang bernilai ekonomis. IAA dapat dihasilkanoleh beberapa mikroba rhizosfer yang mamputumbuh dalam limbah lateks dengan L-triptofan(Trp) sebagai prekursor-nya. Penelitian bertujuanmenetapkan potensi pertumbuhan dan produksiIAA oleh Rhizobium spp. R6 dan KT dalammedium sintetik dan serum lateks yangdisuplementasi Trp sintetik dan kotoran ayamsebagai sumber Trp murah. Isolat potensial dalamproduksi IAA kemudian ditumbuhkan dalammedium serum lateks pekat yang disuplementasiTrp murni dan Trp dari kotoran ayam. Hasilpenelitian menunjukkan bahwa produksi IAAtertinggi diperoleh dalam medium sintetik olehRhizobium sp. R6, sebesar 51,08 µg/mL. IAAdapat diproduksi sebesar 6,63 µg/mL dalammedium serum lateks 100% + Trp 0,14 g/L yangdipasteurisasi. Dalam medium serum lateks yangdisuplementasi Trp dari kotoran ayam, produksiIAA Rhizobium sp. R6 dapat mencapai 11,91µg/mL. Suplementasi Trp murni dalam produksiIAA dapat digantikan dengan kotoran ayamsebagai sumber Trp yang mura